Heterogeneity in Peer Effects of Obesity - Kiersten Strombotne; Sophia Day; Kevin Konty; Jason M. Fletcher (Institute of Labor Economics (IZA), 2024)
Children form social ties along dimensions of gender and race/ethnicity, and thus may differ greatly in exposure to peer health and also in reactivity to peer influence. This paper estimates heterogeneity in the peer effects of obesity along dimensions of gender, race/ethnicity, and socio-economic status for grade-mates within schools. Using data from the New York City (NYC) FITNESSGRAM initiative on over 1.6 million children in grades K-8, we find that males and females are equally responsive to peer effects. We estimate larger differences by race/ethnicity, immigration status and home language, but find no statistically significant differences in peer effects by socio-economic status. Taken together, these findings suggest that policies that reduce obesity could simultaneously widen some existing health disparities due to the heterogeneities in peer effects we uncover. Understanding the dynamics of peer influence is essential for designing policies and programs that seek to leverage social interactions for better health outcomes.
Keywords: 330; peer effects; children; adolescents; obesity; health disparities